Formation of nanocrystalline β structure in metastable beta Ti alloy during high pressure torsion: The role played by stress induced martensitic transformation. (15th September 2015) - Zafari, A.; Wei, X.S.; Xu, W.; Xia, K.
Abstract: High pressure torsion was conducted to obtain nano-sized β grains in a metastable Ti-5553 alloy. Much finer grains of <50 nm were achieved, compared to >100 nm in a stable Ti-20 wt.% Mo alloy. The more effective grain refinement was attributed to stress induced martensitic transformation in the former, leading to the formation of thin α″ plates which divide β grains into smaller domains. Further deformation resulted in a reverse α″ to β transformation with decreasing α″ sizes, generating a completely nano β grain structure at very large straining. A detailed description of the β grain refinement mechanism is provided. The reverse transformation is shown to be caused by the significantly increased free energy below a critical α″ size of ∼10 nm, consistent with experimental observations. It is also calculated that extremely high energies were required for the formation of α″ in nano-sized β grains, making further martensitic transformation impossible. It is concluded that the stress induced martensitic transformation and the subsequent reverse transformation are critical to producing nano-grained metastable β Ti alloys.